Spauligodon azerbajdzanicus sp. n. (Nematode, Pharyngodonidae) — паразит ящерицы зеленобрюхой (Lacerta chlorogaster Bоul.) - Шарпило, В.П. (Вестник зоологии, 1974)
The article deals with the description, drawings and differential diagnosis of the nematode Spauligodon azerbajdzanicus sp. n. found in Lacerta chlorogaster Boul. The new species differs from the closest one-- Spauligodon saxicolae Sharpilo, 1964 fired of all in the length and shape of eggs, presence of a spicule and also in another host